APPLICATION OF PLATELET-RICH PLASMA (PRP) FOR REGENERATION OF VERTICAL BONE DEFECTS - Tsvetalina Gerova-Vatsova; Stefan Peev (Peytchinski Publishing, 2023)
In recent years, there has been a sharp increase in the number of chronic periodontal diseases. The problem of their widespread distribution and the need for their treatment is one of the priorities of modern dentistry. Periodontal bone defects are the result of chronic periodontitis if timely measures are not taken to stop the inflammatory process. The goal of periodontal treatment is to remove all deposits of supra- and subgingival dental plaque and calculus (containing periodontopathogens) and their plaque-retentive factors and to promote complete regeneration of the tooth-supporting structures lost up to that point. Until now, autogenous, platelet-rich plasma has been widely used in various fields of medicine. Because of the equivalent results obtained and the lower cost, in dentistry, autogenous platelet-rich plasma is increasingly the preferred material over others that have proven to be reliable over time. Summarizing the results of various authors who used autogenous platelet-rich plasma alone or in combination with other materials for the purpose of regeneration of vertical bone defects, it is clear that PRP significantly accelerates the restorative and regenerative processes in the periodontium.